Akibat Hukum Dan Pluralisme Hukum Adopsi Di Indonesia - Hadi Adha, Lalu; Asyhadie, H. Zaeni; Kusuma, Rahmawati (Faculty of Law, University of Mataram, 2024)
This article is the result of research and community service on the topic of child adoption in Telaga Waru village, West Lombok. Adoption is not a new problem in our country's legal system. Although the existence of adoption in Indonesia as a legal institution is still not synchronized and still causes various problems in society, child adoption is still widely practiced by our society. Referring to the empirical normative legal research method using a legal sociological approach through direct observation and discussion methods, we argue that although there is pluralism in adoption law, the Telaga Waru community tends to adopt using customary rules that have been in effect for a long time in society compared to the provisions of applicable national law. Likewise, the legal consequences of implementing child adoption that arise both for adoptive parents and for adopted children are not widely known by the public.